2024
DOI: 10.1617/s11527-024-02306-0
|View full text |Cite
|
Sign up to set email alerts
|

Tensile strength retention of glass fibre-reinforced stirrups subjected to aggressive solutions: effect of environmental condition, stirrup shape and stirrup diameter

Amirhossein Hajmoosa,
Mussa Mahmoudi,
Mohsen Ebrahimzadeh
et al.

Abstract: The aim of this study was to examine how the tensile strength of glass fibre reinforced polymer stirrups is affected by different types of solutions, including alkaline, seawater, tap water, and acidic solutions. The study involved the production and testing of 260 stirrups in two different shapes (L and U) with diameters of 6 and 8 mm. The stirrups were immersed in different solutions for a period of 9 months at different temperatures (25, 40, and 60 °C). The findings indicated that the alkaline solution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(76 reference statements)
4
0
0
Order By: Relevance
“…At 20 • C, the UTS slightly improves to 75.50 MPa with an even higher tensile modulus of 13.32 GPa. These results align with the findings in paper [27], which demonstrate that environmental changes from tap water to seawater or alkaline solutions significantly impact tensile strength. Notably, both studies indicate that alkaline environments exert the most substantial effect on reducing tensile strength.…”
Section: Tensile Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…At 20 • C, the UTS slightly improves to 75.50 MPa with an even higher tensile modulus of 13.32 GPa. These results align with the findings in paper [27], which demonstrate that environmental changes from tap water to seawater or alkaline solutions significantly impact tensile strength. Notably, both studies indicate that alkaline environments exert the most substantial effect on reducing tensile strength.…”
Section: Tensile Resultssupporting
confidence: 91%
“…Similarly, the data from [47] showed that temperature significantly impacts the compressive and tensile strength properties of the GFRP material. Our conclusion also aligns with the findings from paper [27], namely, that temperature significantly impacts the strength properties of GFRP materials (p-value < 0.05). The referenced paper [27] also shows that changing the environment from tap water to seawater or alkaline solutions significantly affects tensile strength retention, with alkaline environments having the most substantial The large bar for factor A indicates that temperature significantly affects UTS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations